(3GdGOGQI GdLGeYjI (B:s (3OQGSGJ MOjKI (B/s - (3GdNWjH, GMeOs ((3GQHO(B: s (3YGde GdcJH GdMOjK ddfTQ hGdJhRjY(B, s, 2006)
(3GdYedjI GdGOGQjI h GdeOGQS GdGOGQjI; GdGOGQI GdJQHhjI aj GdhWf GdYQHj(B: (3GdJMOj h BaGb GdeSJbHd GVGaI Gdi GdJYdje GdLGeYj aj GdhWf GdYQHj(B: (3GdJMOjGJ h GdHOGFd GdeSJbHdjI(B, (3GdJYdje GdLGeYj h GdJMhd GdOjebQGWj (B, (3GOGQI GdLGeYGJ aj GdbQf GdMGOj h GdYTQjf(B: (3GSJQGJjLjGJ h feGPL ebJQMI ddGUdGM h GdJWhjQ GdGOGQj(B, (3GdGOGQI GdjGHGfjI h cPG GOGQI GdJZjjQ h GdGHOGY(B, (3GOGQI GdLhOI GdTGedI (B: (3JWHjbGJ aj GdGOGQI GdLGeYjI h GNjQG eSDhdjI GdJYdje GdYGdj aj JWhjQ h GUdGM GdfXGe GdJQHhj(B.s
(3eQGLY U(B.428s
Keywords: (3GdGOGQIs; (3GdJYdje GdYGdjs; (3GdLGeYGJ h GdcdjGJs